Intellectual capital approach to modern management through the perspective of a company’s value added - Tamosiuniene, Rima; Survilaitė, Simona; Shatrevich, Vladimir (Business: Theory and Practice, 2015)
The importance of value creation in small and medium-sized business companies has always been in focus. The changing environment makes a strong impact on all companies all over the world. Nowadays, the value added, which is created by the company, not only depends on tangible but also on intangible assets. It is not enough just to manage internal resources to be efficient or generate high value added. Knowledge and information as an important tool for the management of the external environment have become a new factor of a company. Since elements of the intellectual capital system are intangible and hardly measurable in company’s value added, this paper aims to create a model for the analysis of the creation of a company’s value added through intellectual capital. Subsequent to the review of literature on value creation and management, the authors proposed a model for value creation through intermediate, which presented three main elements of value added creation.